Fodder development in sub-Saharan Africa: An introduction - Boote, K.J.; Adesogan, Adegbola T.; Balehegn, M.; Duncan, Alan J.; Muir, J.P.; Dubeux, J.C.B.; Ríos, E.F. (Wiley, 2022)
Livestock systems play a key role in the sustainability and livelihood of sub‐Saharan Africa (SSA). The human population in SSA is rapidly increasing, resulting in steady growth in the demand for animal‐sourced foods (ASF). Most current agricultural production practices in SSA coupled with poor management, health challenges and indigenous breeds, result in low crop and livestock productivity and often do not meet local demands. To improve productivity, locally adapted technologies and management practices need to be widely adopted. This special issue is a collection of contributions addressing major aspects of crop and livestock systems in SSA. Key topics addressed include the present status of feedstuff availability in SSA, improved fodder production and utilization practices, new cultivars, soil management, forage conservation, use of near infrared reflectance spectroscopy (NIRS) tools to measure forage nutritive value, and social and economic aspects of crop‐livestock systems. The overarching goal of this special issue is to provide insightful information that can be used for the future development and implementation of efficient and sustainable integrated systems. SSA will have a key role in feeding itself and the world in the future, and livestock systems and cropping practices are crucial components of this process.